Fonti e tradizioni culturali nella corrispondenza di Francesco Filelfo: nuove indagini e percorsi metodologici - I. Tessere virgiliane (Quaderni di Gargnano, 2018)
This is a broad survey of the Virgilian echoes in Filelfo’s Latin letters, which are divided into paragraphs corresponding to the different elements that Filelfo included as part of his perpetual desire to support his opinions with reference to classical “auctoritas” (prosody, grammar, vocabulary, allegorical readings, etc.). New sources are mined from previous commentaries on Virgil, such as those of Servius in late antiquity or Bernardus Silvestris in the 12th century.
Keywords: Servius; Vergil; epistolography; classical tradition; Humanism